Prognostic impact of white blood cell counts on clinical outcomes in patients with chronic renal insufficiency undergoing percutaneous coronary intervention - Yan, Wei; Li, Mengyao; Lei, Yumeng; Zhang, Shuaiyong; Lv, Fengfeng; Wang, Jiawang; Yang, Qian; Yu, Na; Chen, Ming; Cao, Xufen; Yan, Liqiu (Frontiers in Cardiovascular Medicine, 2023)
Objective: To determine whether the inclusion of white blood cell (WBC) counts in the SYNTAX score (SS) or SS II models could improve the models’ performance for risk stratification in individuals with chronic renal insufficiency (CRI) following percutaneous coronary intervention (PCI). Methods: In total, 2313 patients with CRI, who were subjected to PCI and had data available on in-hospital WBC (ih-WBC) counts, were recruited. Patients were divided into 3 groups as per their ih-WBC counts (low, medium, and high). The primary endpoints were all-cause mortality (ACM) and cardiac mortality (CM). The secondary endpoints incorporated myocardial infarction, stroke, unplanned revascularization, and major adverse cardiovascular and cerebrovascular events (MACCEs). Results: During a median follow-up of 3 years, the high WBC group had the highest incidences of CM (2.4% vs. 2.1% vs. 6.7%; p<0.001), ACM (6.3% vs. 4.1% vs. 8.2%; p<0.001), unplanned revascularization (8.4% vs. 12.4% vs. 14.1%; p<0.001), and MACCEs (19.3% vs. 23.0% vs. 29.2%; p<0.001) among the three groups. Multivariable Cox regression analysis depicted that the risk of ACM and CM in the high WBC group was 2.577 (95% confidence interval [CI]: 1.504–4.415, p<0.001) and 3.850 (95% CI: 1.835-8.080, p<0.001) times that in the low WBC group after adjusting for other confounding factors. A combination of ih-WBC counts with SS or SS II significantly improved the risk assessment and prediction of ACM and CM. Conclusions: The ih-WBC counts was associated with the risk of occurrence of ACM, CM, unplanned revascularization, and MACCEs in individuals with CRI following PCI. It provides an incremental predictive value for the occurrence of ACM and CM when included in SS or SS II models.